Characteristics of euthyroid sick syndrome in patients with breast cancer - E. M. Frantsiyants; V. A. Bandovkina; L. N. Vashchenko; S. S. Todorov; N. D. Cheryarina; A. M. Salatova; L. P. Kuchkina; E. S. Bosenko; N. S. Saforyan; N. D. Ushakova (Исследования и практика в медицине)
Purpose. Determination of thyroid hormones (TH) and cortisol levels in blood in patients with breast cancer (BC) without previously detected endocrine pathology in the anamnesis.Patients and methods. Twenty-ﬁve primary luminal A breast cancer patients before and aﬅer surgical removal of the tumour and 25 breast cancer patients with secondary metastatic brain lesions were examined. The levels of total and free forms of TH (T4, FT4, T3 FT3) and cortisol were determined in serum by RIA method.Results. Before treatment in all patients with breast cancer the level of T3 was decreased 1.3 times and FT3 was increased 1.3 times (p < 0.05) against the background of normal TTH content. In 80 % of patients, blood cortisol concentration was 2 times higher than normal, and in 16 % of patients, T4 level was 1.8 times higher than normal (p < 0.05). Aﬅer tumour removal, FT3 levels in all patients and cortisol levels in 40 % of patients did not diﬀer from normal. T4 content in 40 % of patients, and T3 and TTH in 28 % of women were above normal. A distinctive feature of patients with brain metastases of breast cancer was low T4 and cortisol levels in 36 % of patients against the background of low T3 levels.Conclusions. Euthyroid sick syndrome was detected in all patients with BC: low serum T3 levels against the background of normal serum levels of TTH. Patients with primary BC were characterized by high concentrations of FT3 and cortisol, which could promote proliferation of malignant cells and decrease antitumour immunity. The condition of 1/3 of patients with brain metastases was aggravated by low levels of T4 and cortisol which could indicate the depletion of the main regulatory systems and an unfavorable disease prognosis.